Global connections from Bandung: youth forum as a new pillar of city paradiplomacy: Koneksi global dari Bandung: youth forum sebagai pilar baru paradiplomasi kota - Windy Dermawan; Ilham Shidqi Nurrahmadi; RMT Nurhasan Affandi (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2025)
This research aims to analyze the forms and levels of youth participation in supporting the implementation of paradiplomacy in the City of Bandung through the Bandung Sister Cities (Basic) Youth Forum, particularly in the sister city relationship between Bandung and Braunschweig. Using a descriptive-analytical qualitative approach, data were collected through in-depth interviews, online searches, and document reviews, and verified through triangulation techniques. This research is based on the participation theory by Cohen & Uphoff (1977) and Roger Hart's ladder of participation model (1992), as well as the concept of paradiplomacy by Kuznetsov and Tavares. The research results show that the participation of the Basic Youth Forum is classified as participation in implementation, where the youth are involved in the technical execution of paradiplomacy activities, but not yet in the planning or policy evaluation stages. The level of participation falls into the category of adult-initiated, shared decisions with youth, meaning the initiative comes from adult actors (government agencies), but involves youth in the decision-making process of activity implementation. These findings underscore the importance of strengthening participatory structures in regional paradiplomacy, including the formulation of concrete work plans to ensure that youth involvement is not merely symbolic. Thus, the Basic Youth Forum has the potential to become a strategic pillar in more inclusive and sustainable city diplomacy.